Analysis Of Working Capital Credit Provision System And Handling Of Bad Credit (Case Study At PT. BPR Supra Artapersada Pelabuhan Ratu Branch): - Wijaya, Arip Prilian; Kartini, Tina; Nurodin, Idang (Universitas Dehasen Bengkulu, 2024)
This study aims to analyze the working capital credit provision system and the handling of bad credit at PT. BPR Supra Artapersada Pelabuhan Ratu Branch. The data used includes qualitative data in the form of credit applications, credit guidelines, credit analysis, credit agreements, warning letters, and the organizational structure of PT. BPR Supra Artapersada Pelabuhan Ratu along with its job descriptions. Data collection techniques involve observation, interviews, and documentation, which are then analyzed using qualitative descriptive analysis. The results of this study indicate that the working capital credit provision system implemented at PT. BPR Supra Artapersada is generally good, with a structured procedure from credit application, credit analysis, approval, to disbursement. However, some aspects still require improvement to prevent bad credit. The handling of bad credit at PT. BPR Supra Artapersada is also quite comprehensive, including initial notifications, direct communication, field visits, issuing warning letters, and applying the 3R methods (Restructuring, Rescheduling, Reconditioning). However, there is a need to improve the mechanism for seizing collateral and to adjust the legal procedures applied.